A Survey Integration of Wearable Device with Block Chain Technology in the Healthcare - M, Sathishkumar; Raghavendran, V. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This survey aims to explore the synergies between wearable devices, EHRs, and block chain technology in the context of generating digital passports. By examining the current state of research, technological advancements, and real-world implementations, the survey seeks to provide a comprehensive understanding of the opportunities, challenges, and implications of this innovative intersection. Through this exploration, we aim to contribute insights that will propel the integration of wearable’s and block chain-secured EHR digital passports into mainstream healthcare, fostering a future where individuals have greater agency over their health data and healthcare providers are empowered with more comprehensive and timely information for improved patient care.